2021
DOI: 10.2215/cjn.16821020
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oral Energy-Dense Supplements on Nutritional Status in Nondiabetic Maintenance Hemodialysis Patients

Abstract: Background and objectives: Fat-based energy-dense nutritional supplements may offer benefits over protein or carbohydrate dense supplements for patients receiving dialysis because of the adverse metabolic consequences of the latter. We conducted a randomized controlled trial to assess the effects of the short-term use of a fat-based nutritional supplement on various measures of nutritional status in patients receiving maintenance hemodialysis who have low dietary energy intake. Design, setting, participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…In accordance with the present results, Allman et al 12 concluded that the addition of glucose polymer to the diet could increase the weight of MHD patients with low BMI. Nonetheless, contrary to our expectation, Yang et al 17 evaluated the efficacy of three-month administration of an oral energy-dense protein-free nutritional supplement (300 kcal, fat-based) among 240 MHD patients with low energy intake, and no significant effect was recognized on the nutritional status, which is conflicting with the current study. This incon- Nutritional supplementation was considered to increase energy intake and improve the nutritional status of patients as inadequate energy intake was the main contributor to PEW in MHD patients.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…In accordance with the present results, Allman et al 12 concluded that the addition of glucose polymer to the diet could increase the weight of MHD patients with low BMI. Nonetheless, contrary to our expectation, Yang et al 17 evaluated the efficacy of three-month administration of an oral energy-dense protein-free nutritional supplement (300 kcal, fat-based) among 240 MHD patients with low energy intake, and no significant effect was recognized on the nutritional status, which is conflicting with the current study. This incon- Nutritional supplementation was considered to increase energy intake and improve the nutritional status of patients as inadequate energy intake was the main contributor to PEW in MHD patients.…”
Section: Discussioncontrasting
confidence: 86%
“…Nonetheless, contrary to our expectation, Yang et al 17 Nutrition support was considered to increase energy intake and improve nutritional status of patients as inadequate energy intake was the main contributor to PEW in MHD patients 4,25 . Noteworthily, in this study, the SGA score of patients in intervention group was significantly higher compared with control at the end of the study, suggesting that the oral non-protein calorie supplements had a positive influence on the nutritional status of MHD patients.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, many patients fail to comply with these recommendations due to dietary restrictions, anorexia, and socioeconomic limitations (Wu et al, 2013;Sabatino et al, 2018;Bolasco, 2020). Additional intervention is needed to aid patients in achieving therapeutic nutritional energy goals, in which oral energy supplements (OESs) may offer benefits over protein-or carbohydrate-dense supplements for patients undergoing dialysis because of the adverse metabolic consequences of the latter (Yang et al, 2021). However, previous studies had considered oral nutritional supplements, which contain proteins and electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines strong recommended nutritional interventions in MHD patients [10]. However, evidence regarding the effects of oral nutritional supplements (ONS) on the nutritional status of MHD patients is insu cient and inconsistent [11][12][13][14]. Most of the ONS used in previous studies were amino acid or protein-based supplements.…”
Section: Introductionmentioning
confidence: 99%